Expanding an Economic Evaluation of the Veterans Affairs (VA) Methicillin-resistant Staphylococcus aureus (MRSA) Prevention Initiative to Include Prevention of Infections From Other Pathogens. (29th January 2021) - Nelson, Richard E; Goto, Michihiko; Samore, Matthew H; Jones, Makoto; Stevens, Vanessa W; Evans, Martin E; Schweizer, Marin L; Perencevich, Eli N; Rubin, Michael A
Abstract: Background: In October 2007, Veterans Affairs (VA) launched a nationwide effort to reduce methicillin-resistant Staphylococcus aureus (MRSA) transmission called the National MRSA Prevention Initiative. Although the initiative focused on MRSA, recent evidence suggests that it also led to a significant decrease in hospital-onset (HO) gram-negative rod (GNR) bacteremia, vancomycin-resistant Enterococci (VRE), and Clostridioides difficile infections. The objective of this analysis was to evaluate the cost-effectiveness and the budget impact of the initiative taking into account MRSA, GNR, VRE, and C. difficile infections. Methods: We developed an economic model using published data on the rate of MRSA hospital-acquired infections (HAIs) and HO-GNR bacteremia in the VA from October 2007 to September 2015, estimates of the attributable cost and mortality of these infections, and the costs associated with the intervention obtained through a microcosting approach. We explored several different assumptions for the rate of infections that would have occurred if the initiative had not been implemented. Effectiveness was measured in life-years (LYs) gained. Results: We found that during fiscal years 2008–2015, the initiative resulted in an estimated 4761–9236 fewer MRSA HAIs, 1447–2159 fewer HO-GNR bacteremia, 3083–3602 fewer C. difficile infections, and 2075–5393 fewer VRE infections. The initiative itself was estimated to cost 561 million over this 8-year period, whereas the cost savings from prevented MRSA HAIs ranged from 165 to 315 million and from prevented HO-GNR bacteremia, CRE and C. difficile infections ranged from 174 to 200 million. The incremental cost-effectiveness of the initiative ranged from 12 146 to 38 673/LY when just including MRSA HAIs and from 1354 to 4369/LY when including the additional pathogens. The overall impact on the VA's budget ranged from 67 to195 million. Conclusions: An MRSA surveillance and prevention strategy in VA may have prevented a substantial number of infections from MRSA and other organisms. The net increase in cost from implementing this strategy was quite small when considering infections from all types of organisms. Including spillover effects of organism-specific prevention efforts onto other organisms can provide a more comprehensive evaluation of the costs and benefits of these interventions. Abstract : This study evaluated the cost-effectiveness and the budget impact of the VA MRSA Prevention Initiative taking into account MRSA, GNR, VRE, and C. difficile infections. Including spillover effects of organism-specific prevention efforts onto other organisms is important.